Perceived parenting style and mother’s behavior in maintaining dental health of children with Down syndrome - Siti Fitria Ulfah; Darmawan Setijanto; Taufan Bramantoro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: The number of children with down syndrome in Surabaya has reached 924 children. Prevalence of gingivitis and dental caries (91% and 93.8%, respectively) occurs in children with down syndrome aged 6 to 20 years. Oral and dental health problems are found in children with down syndrome because they have physical and motoric limitation in maintaining oral and dental hygiene, thus require parental care from mother. Perceived parenting style includes responsiveness and demandingness. Perceived parenting is crucial for mother whose children have Down syndrome in order to guide their health behavior, particularly to maintain oral and dental health. Purpose: The study aimed to analyze correlation between perceived parenting style and mother’s behavior in maintaining dental health of children with Down syndrome. Method: This cross sectional analytical study involved 40 mothers of children aged 7-13 years with Down syndrome enrolled in Special Education Elementary Schools Surabaya and Association of Parents of Children with Down syndrome Surabaya. Data of perceived parenting style (responsiveness and demandingness) and mother’s behavior in maintaining dental health were obtained by questionnaire. Composition of each item in questionnaire of perceived parenting style and mother’s behavior in maintaining dental health of children with Down syndrome was passed through validity and reliability test. Data analysis was carried out using multiple linear regression correlation test. Result: This present study showed that perceived parenting style is significantly correlated with mother’s behavior in maintaining dental health of children with Down syndrome (R = 0.630, p = 0.000), with perceived parental responsiveness as a strong predictor. Mean score and standard deviation of perceived parental responsiveness and demandingness were 33.00±2.99 and 15.55±1.99, respectively. Conclusion: Perceived maternal parenting style in children with Down syndrome is closely related to mother’s behavior in maintaining dental health of children with Down syndrome.